Ensuring transcript integrity with SHA-3 and digital signature standard: a practical approach - Nur Alam, Wa Ode Siti; Sajiah, Adha Mashur; Bahtiar Aksara, La Ode Muhammad; Surimi, La; Ransi, Natalis; Nangi, Jumadil (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Academic transcripts are essential documents in higher education, reflecting students’ academic performance and capabilities. However, the current management of transcript data at Halu Oleo University (UHO) lacks safeguards against unauthorized alterations, compromising their authenticity. This study proposes a method using the secure hash algorithm 3 (SHA-3) and the digital signature standard (DSS) scheme to ensure the integrity of transcript data. A Python-based web module for managing transcripts and a signing program using SHA-3 and DSS were developed and implemented. This method digitally signs transcript files, ensuring that subsequent changes invalidate the current digital signature. Efficiency tests demonstrated an average signing time of 0.242 seconds, indicating a practical and efficient solution. The study’s findings emphasize how SHA-3 and DSS effectively authenticate academic transcript files, preventing unauthorized modifications and safeguarding the integrity of critical educational records. This method presents a robust and efficient solution for educational institutions to strengthen the security and reliability of their academic record management systems.